The effect of aquatic exercise on physical functioning in the older adult: a systematic review with meta-analysis - Waller, Benjamin; Ogonowska-Słodownik, Anna; Vitor, Manuel; Rodionova, Karina; Lambeck, Johan; Heinonen, Ari; Daly, Daniel (Age and ageing, 2016)
ageing and sedentary behaviour cause negative changes in the neuromuscular systems of healthy older adults resulting in a decrease in physical functioning. Exercising in water (aquatic exercise, AE) has been shown to be effective at improving physical functioning in this population; however, no systematic review with meta-analysis has been published. to investigate the effect of AE on physical functioning in healthy older adults compared to control or land-based exercise (LE) through a systematic review with meta-analysis of randomised controlled trials. Medline, Embase, Cinahl, PEDro, SPORTDiscus, Web of Science, Cochrane Library, published before 31st December 2015. in total, 28 studies met the inclusion criteria and were included in the systematic review; 24 studies with 1,456 subjects (89% female) and with mean age 66.4 years were included in the meta-analysis. data were extracted and checked for accuracy by three independent reviewers. size of treatment effect was measured using the standardised mean difference with 95% confidence intervals (CIs). compared to control interventions, AE had a moderate positive effect on physical functioning 0.70 [95% CI 0.48 to 0.92]. Compared to LE, AE had a small positive effect on physical functioning 0.39 [0.12 to 0.66]. there is a high risk of bias and low methodological quality in the studies particularly when comparing AE to LE with possible over estimation of the benefit of AE. AE may improve physical functioning in healthy older people and is at least as effective as LE.